Asymmetries Across Regional Housing Markets in Turkey - Duran, Hasan Engin; Duran, Hasan Engin; Özdoğan, Hilal (Elsevier, 2020)
In the literature on real estate prices, two main groups of determinants are primarily considered; speculative and fundamental variables. Empirical literature in the areas has, however, several shortcomings. First, although existing studies have analysed the role played by speculative factors, none of the studies, have measured precisely the relative importance of speculative and fundamental variables. We aim at doing this. Moreover, the literature has measured the speculation only by analysing backward-looking behavior. We improve this analysis by considering also forward-looking expectations. Second, in terms of cross-regional determinants, the literature has largely considered economic and demographic variables whereas geographical and cultural variables have been ignored. We intend to incorporate them. Hence, aim of this paper is to understand the dynamics behind the housing prices in 26 Turkish regions between 2010:1–2016:9. We employ range of econometric methods such as Vector-Autoregressions, Unit Root Analysis, Cholesky Forecast Error Variance Decompositions, Impulse-Response Functions, Panel Regressions, Lagrange Multiplier Spatial Dependence Tests and Granger Causality Tests. As an outcome, three results emerge. First, housing price appreciations are so heterogeneous across regions. Second, role of speculative behaviour is quite significant. Third, regions which have high urbanization, population, crime rate, trade openness, seaside and cultural density experience faster housing appreciations. © 2020 Elsevier B.V.
Keywords: Fundamental variables; Panel regression; Regional housing price determinants; Speculation; Vector autoregression